2011
DOI: 10.1177/0885066610392499
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation Bundle Compliance in Severe Sepsis and Septic Shock

Abstract: Initiating the sepsis RB for patients with severe sepsis and/or septic shock decreased mortality. A CQI initiative that monitored the implementation in real-time allowed for improvement in compliance and efficacy of the bundle on outcomes. Multiple studies have shown that compliance to the RB within 6 hours lowers hospital mortality. This study uniquely shows that when bundle completion is extended to 18 hours, the mortality reduction remains significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…One study by Kumar et al demonstrated improved compliance to the sepsis six (oxygen, blood cultures, antibiotics, lactate measurement, intravenous fluids, and urine output monitoring) from 29% pre-intervention to 63% post-intervention, but without demonstrable improvement in outcomes [18]. However, most studies indicate improved outcomes even with modest adherence to bundled care [9] [1922]. Our program was similar to others with regards to provision of the 3-hour bundle, with our institution adding components of education, electronic recognition, designated response teams, and RRT.…”
Section: Discussionmentioning
confidence: 99%
“…One study by Kumar et al demonstrated improved compliance to the sepsis six (oxygen, blood cultures, antibiotics, lactate measurement, intravenous fluids, and urine output monitoring) from 29% pre-intervention to 63% post-intervention, but without demonstrable improvement in outcomes [18]. However, most studies indicate improved outcomes even with modest adherence to bundled care [9] [1922]. Our program was similar to others with regards to provision of the 3-hour bundle, with our institution adding components of education, electronic recognition, designated response teams, and RRT.…”
Section: Discussionmentioning
confidence: 99%
“…25 On the contrary, in 498 patients with severe sepsis or septic shock, compliance with a sepsis resuscitation bundle at 18 hours demonstrated a significant mortality benefit with mortality decreased from 47.3% to 37.1%. 26 …”
Section: Discussionmentioning
confidence: 99%
“…Schramm et al implemented weekly feedback to care teams regarding their compliance in addition to starting a sepsis response team. Similarly, Coba et al showed that monitoring the implementation of the resuscitation bundle elements by a continuous quality initiative, resulted in improvements in compliance and mortality (Coba et al 2011).…”
Section: Introductionmentioning
confidence: 99%